1993
DOI: 10.2527/1993.7161526x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and pineal neurochemicals in steers grazed on endophyte-infected tall fescue: effects of metoclopramide1

Abstract: Plasma and pineal melatonin (MEL) and selected pineal neurochemicals (5-hydroxytryptophan, serotonin, N-acetylserotonin, dopamine, norepinephrine) associated with MEL synthesis were determined in steers grazing Acremonium coenophialum (endophyte)-infected 'Kentucky-31' tall fescue paddocks. Paddock treatments included low (LE, 33%) or high (HE, 74%) endophyte at either low (134 kg.ha-1 x yr-1, LN) or high (335 kg.ha-1 x yr-1, HN) nitrogen fertilization. Twelve pairs of yearling Angus steers were randomly assig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…For example, while melatonin was not directly measured, metabolites derived from it were increased in the urine (i.e., AFMK) and decreased in the plasma. Decreased plasma melatonin in E+, which would be consistent with the findings here, has been reported (Porter et al, 1993). AFMK is the product of the reaction between melatonin and reactive oxygen species (ROS; de Almeida et al, 2003;Hardeland et al, 1995;Tan et al, 2000), and previous reports found widespread decreased antioxidant defense mechanisms due to E+ (Lakritz et al, 2002;Settivari et al, 2008;Zbib et al, 2014Zbib et al, , 2015.…”
Section: Accepted Manuscriptsupporting
confidence: 92%
“…For example, while melatonin was not directly measured, metabolites derived from it were increased in the urine (i.e., AFMK) and decreased in the plasma. Decreased plasma melatonin in E+, which would be consistent with the findings here, has been reported (Porter et al, 1993). AFMK is the product of the reaction between melatonin and reactive oxygen species (ROS; de Almeida et al, 2003;Hardeland et al, 1995;Tan et al, 2000), and previous reports found widespread decreased antioxidant defense mechanisms due to E+ (Lakritz et al, 2002;Settivari et al, 2008;Zbib et al, 2014Zbib et al, , 2015.…”
Section: Accepted Manuscriptsupporting
confidence: 92%
“…A retrospective analysis of nine previously reported datasets revealed daylength was positively correlated with E. coli prevalence . Steers grazing endophyte-infected tall fescue had decreased plasma concentrations of melatonin (Porter et al, 1993). Recently, Edrington et al (2007) reported fecal shedding of E. coli O157:H7 from naturally infected steers was decreased in steers receiving melatonin.…”
Section: Discussionmentioning
confidence: 98%
“…Maternal hyperthermia in pregnant mice has been shown to increase embryonic death via an increase in oxidative stress, while melatonin injections alleviated this effect by maintaining a neutral redox status [ 57 ]. Cattle grazing endophyte-infected fescue exhibit decreased plasma melatonin [ 58 , 59 ], rough hair coats, and vasoconstriction to peripheral tissues, limiting heat dissipation and increasing body temperature [ 50 , 60 ]. Based on these findings, it is suggested to further investigate the role of melatonin and its usage as a therapeutic in domesticated farm animals experiencing cardiovascular diseases and hyperthermia.…”
Section: Circadian Rhythms Environmental Factors and Body Temperaturementioning
confidence: 99%